Monetary shocks and stock returns: Identification through the impossible trinity - Ali K. Ozdagli; Yifan Yu (Federal Reserve Bank of Boston, 2012)
This paper attempts to identify how monetary policy shocks affect stock prices by using Mundell and Fleming's theory of the Impossible Trinity. According to this theory, it is impossible to simultaneously have a fixed exchange rate, free capital movement (an absence of capital controls), and an independent monetary policy. The authors present evidence that Hong Kong's monetary policy is heavily dependent on the monetary policy of the United States, a stance which is consistent with this theory because the HK dollar has been pegged to the U.S. dollar since 1983 and Hong Kong does not impose any capital controls. As a result, the Federal Reserve's monetary policy actions can be considered as exogeneous shocks to the Hong Kong economy. Recognizing this relationship helps us solve the endogeneity problem inherent in the studies examining the relationship between stock prices and monetary policy shocks. This is the first paper that presents evidence of severe omitted variable bias in the event studies focusing on the relationship between monetary policy and stock returns. The authors also suggest a way to remedy this bias.
Keywords: E44; E52; E58; G12; G15; G18; 330; stock prices; monetary policy; simultaneity; omitted variables